Perbaikan Keseimbangan Lintasan di Lini Produksi ECOSS Perusahaan Heat Exchanger - Ardityo Irawan (Jurnal Titra, 2017)
PT XYZ is one of the company that produce heat exchanger in Indonesia. The Company developing a new production line for a new product, which is ECOSS product. The Company demanding an effective and efficient process of ECOSS production line design. The design analyse production line with line balancing method. Line balancing analysis purposed for balancing the production line, also increase the production output and minimalize labor cost. Line balancing done by optimizing amount of labor. The improvement design can increase production output and lower the labor cost. Production output per month increased by 101.4% and labor cost lowered to Rp 1,382,320/product from the initial labor cost Rp 1,988,614/product.